Fabrication of Large‐Area Bimodal Sensors by All‐Inkjet‐Printing. Issue 4 (6th February 2019) - Fu, Sheng; Tao, Juan; Wu, Wenqiang; Sun, Junlu; Li, Fangtao; Li, Jing; Huo, Zhihao; Xia, Zhiguo; Bao, Rongrong; Pan, Caofeng
Abstract: Electronic skin (e‐skin) is a wearable smart terminal that senses changes of external environment like human skin. It will develop into an indispensable way of interaction between humanity and technology. Here, this bimodal e‐skin that senses bending strain and pressure using an all‐inkjet‐printing method is synthesized. It is based on a microcracked metal film and a sandwich capacitor structure. It is characterized by the metal film of the strain sensor as a bottom electrode of pressure sensor; the electrode plate of the device plays a dual role. When tested, the strain sensor and pressure sensor do not interfere with each other. The device has excellent performance with low pressure‐detection of 2 Pa and high stability over more than 5700 cycles for pressure sensor and high gauge factor (4000) and good stability (over 4500 cycles) for strain sensor, which can recognize the radius of curvature of human activities and objects, and can detect the pressure distribution and the curvature of irregular surfaces, showing its potential applications in wearable devices. Abstract : A bimodal sensor is fabricated using an all‐inkjet‐printing method. The sensor can sense pressure and bending strain, simultaneously. Then, an array is prepared to sense pressure distribution and curved surface of irregular surfaces. Based on inkjet‐printing, the work is expected as a foreshadowing to create simple and multimodal electronic skins.